2017
DOI: 10.1080/1744666x.2017.1285699
|View full text |Cite
|
Sign up to set email alerts
|

Standard and biological treatment in large vessel vasculitis: guidelines and current approaches

Abstract: Giant cell arteritis and Takayasu arteritis are the two major forms of idiopathic large vessel vasculitis. High doses of glucocorticoids are effective in inducing remission in both conditions, but relapses and recurrences are common, requiring prolonged glucocorticoid treatment with the risk of the related adverse events. Areas covered: In this article, we will review the standard and biological treatment strategies in large vessel vasculitis, and we will focus on the current approaches to these diseases. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…syndrome (93),vasculitis (94),andgraft-versus-hostdisease (95)-canbetreatedbyblockingtheactionofIL-6 (96,97). Monoclonal anti-IL-6 antibodies have previously been developed to inhibit the signal transduction of IL-6, but this strategy failed in the initial clinical trials.…”
Section: Therapeutic Effects Of Inhibiting Il-6 Action In Sscmentioning
confidence: 99%
“…syndrome (93),vasculitis (94),andgraft-versus-hostdisease (95)-canbetreatedbyblockingtheactionofIL-6 (96,97). Monoclonal anti-IL-6 antibodies have previously been developed to inhibit the signal transduction of IL-6, but this strategy failed in the initial clinical trials.…”
Section: Therapeutic Effects Of Inhibiting Il-6 Action In Sscmentioning
confidence: 99%
“…TNF-α blockers are ineffective in giant cell Arteritis, while observational evidence and a phase 2 randomized trials support the use of tocilizumab in relapsing giant cell arteritis. Observational evidence strongly supports the use of anti-TNF-α agents and tocilizumab in TA patients with relapsing disease [15].…”
Section: Resultsmentioning
confidence: 89%
“…1 Early therapy contributes to the prevention of TA complications (aortic regurgitation, congestive heart failure, renal hypertension, or stroke). Recent studies have suggested that anti-tumor necrosis factor-a biological therapies were highly effective in treating TA refractory to conventional immunosuppressive therapy (corticosteroids, methotrexate) 2 .…”
Section: Answer To: Image 1 (Page 2055): Takayasu Arteritismentioning
confidence: 99%